(untitled) (International Journal of Engineering and Computer Science, 2017)
The timing pathway is a fully-organized pathway for exchanging the ideas in which they are encoded by the timing within events. Absolutely, whilst a jammer has the power to disorganize the data gathered in the stormed packets. Timing data is not able to be jammed. As long as on a blocked pathway the data can deliver to the acceptor and achieve their results. The transmission located in the wireless midway is determined by the familiar attack called as jamming attack. Below this attack, because the knot join with the jammer have contrary interests, their communications can be designed by the method of game theory. Correspondingly, in this summary a game theoretic imitation of the interplay among nodes with the help of timing pathways to attain flexibility to jamming intrusion along with a jammer copied and guessed. Especially, the Nash equilibrium is analyzed in some kinds of time period, singleness, and merging below best response dynamics. Moreover, the case in whatever the interacting nodes decide their plan of action join with the jammer respond correspondingly is designed and estimate as a stackelberg game, by in the view of a pair the perfect and imperfect acquaintance of the jammers efficiency function. It will show the collision of network framework on the arrangement performance.